Estimating mortality impacts from vehicle emission reduction efforts: The Tune In and Tune Up program in the San Joaquin Valley. (January 2020) - Connolly, Rachel; Pierce, Gregory; Gattaciecca, Julien; Zhu, Yifang
Highlights: The public health impacts of an innovative smog repair program were assessed. Different methods were used to assess tailpipe emission reductions. Approximately 53–302 tons of NOX emissions were avoided from the program. The related ambient PM2.5 associated mortality was 0.055–0.31 premature deaths. Abstract: As a response to profoundly poor air quality and associated environmental justice concerns in the San Joaquin Valley region in California, the Tune In & Tune Up (TI&TU) program provides residents with free vehicle emissions testing and vouchers for smog repair. We used data on approximately 19, 000 repaired TI&TU vehicles from 2012 to 2018, and several estimation techniques, to quantify a range of nitrogen oxides (NOX ) emissions prevented as a result of the program. We then calculated resulting mortality impacts from reduced exposure to fine particulate matter (PM2.5 ) in the form of secondary nitrates. After applying a novel smog repair emissions abatement depreciation function, we find that six years of operation of the TI&TU program has reduced NOX emissions by approximately 53–302 tons by the end of 2018. Using a concentration response function for ambient PM2.5, we found that between 0.055 and 0.31 premature deaths have also been avoided. We present multiple methods for assessing public health impacts, which can be used as guidance for evaluating similar transportation-based emission reduction programs.